2008
DOI: 10.1002/elps.200800039
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐high‐performance liquid chromatography platform for the depletion of high‐abundance proteins and subsequent on‐line concentration/capturing of medium and low‐abundance proteins from serum. Application to profiling of protein expression in healthy and osteoarthritis sera by 2‐D gel electrophoresis

Abstract: In this investigation, an integrated microcolumn-based fluidic platform for the simultaneous depletion of high-abundance proteins and the subsequent on-line concentration/capturing of medium- and low-abundance proteins from human serum has been introduced. The platform consists of on-line coupling of tandem affinity micorcolumns to an RP microcolumn to achieve first the depletion of high-abundance proteins by the tandem affinity microcolumns followed by the concentration and capturing of medium- and low-abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Analysis of serum samples from OA patients in a large populationbased study has identified an autoantibody to triosephosphate as a novel marker that could be used as a diagnostic biomarker for OA (139). A comparison of 2D protein profiles of serum from healthy individuals, OA patients and OA patients taking soy supplements (a source of anti-inflammatory compounds such as genistein) has been completed to assess the differential proteins (140). The OA serum provided evidence of altered levels of proteins including vitamin D-binding protein precursor and apolipoprotein A-I and A-IV precursors.…”
Section: Oa Biomarkers In Body Fluids: Proteomic Studies Of Urinary Amentioning
confidence: 99%
“…Analysis of serum samples from OA patients in a large populationbased study has identified an autoantibody to triosephosphate as a novel marker that could be used as a diagnostic biomarker for OA (139). A comparison of 2D protein profiles of serum from healthy individuals, OA patients and OA patients taking soy supplements (a source of anti-inflammatory compounds such as genistein) has been completed to assess the differential proteins (140). The OA serum provided evidence of altered levels of proteins including vitamin D-binding protein precursor and apolipoprotein A-I and A-IV precursors.…”
Section: Oa Biomarkers In Body Fluids: Proteomic Studies Of Urinary Amentioning
confidence: 99%
“…Jmeian et al , have described a novel LC system enabling capture of proteins from the depletion via a reversed phase material optimized for injections of circa 25 µL plasma [18]. In a subsequent paper he further refined the methodology, employing tandem affinity columns for the depletion and fractionation of low-abundance plasma proteins by tandem immobilized metal-ion affinity chromatography columns and capture on reversed phase (RP) column [19].…”
Section: Introductionmentioning
confidence: 99%